AGK2 ameliorates mast cell-mediated allergic airway inflammation and fibrosis by inhibiting FcεRI/TGF-β signaling pathway. (September 2020) - Kim, Yeon-Yong; Hur, Gayeong; Lee, Seung Woong; Lee, Seung-Jae; Lee, Soyoung; Kim, Sang-Hyun; Rho, Mun-Chual
Graphical abstract: Highlights: Effects of SIRT2 on mast cell activation remain to be elucidated. AGK2, an SIRT2 inhibitor, was used for this purpose. AGK2 inhibits mast cell degranulation by suppressing the FcεRI signalling pathway. AGK2 reduces levels of pro-inflammatory cytokines. AGK2 is a candidate for treating mast cell-mediated allergic airway inflammation. Abstract: Asthma is characterized by airway hyperresponsiveness and allergic inflammation, detrimentally affecting the patients' quality of life. The development of new drugs for the treatment of asthma is warranted to alleviate these issues. Recent studies have demonstrated that sirtuin2 (SIRT2) aggravates asthmatic inflammation by up-regulation of T-helper type 2 responses and macrophage polarization. However, effects of SIRT2 on mast cell activation remain obscure. In this study, we investigated the effects of AGK2, an inhibitor for SIRT2, on mast cell-mediated allergic airway inflammation. Pre-treatment with AGK2 inhibited degranulation of mast cells by suppressing the FcεRI signaling pathway and intracellular calcium influx. The expression of pro-inflammatory cytokines, such as tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-4, IL-5, IL-6, and IL-8, was inhibited via regulation of transcription factors such as NF-κB and NRF2. These effects of AGK2 were verified in passive cutaneous anaphylaxis and acute lung injury animal models. AGK2 attenuated Evans blue pigmentation by inhibiting mast cell activation and lung barrier dysfunction by inhibiting inflammatory responses in these animal models. In the ovalbumin (OVA)-induced allergic airway inflammation murine model, AGK2 alleviated allergic asthma symptoms such as lung histological changes (immune cell and mast cell infiltration, collagen deposition, and α-smooth muscle actin expression) and serum immunoglobulins (Ig) levels (IgE, OVA-specific IgE, IgG1, and IgG2a). Moreover, AGK2 reduced the levels of pro-inflammatory cytokines (TNF-α, IL-1β, IL-4, IL-5, and IL-6) and inflammatory mediators (myeloperoxidase, eosinophil peroxidase, and tumor growth factor-α) in the bronchoalveolar lavage fluid and lung tissues. In addition, the anti-fibrotic effects of AGK2 were verified using lung epithelial cells and TGF-β/Smad reporter stable cells. In conclusion, our findings suggest that SIRT2 plays a role in mast cell-mediated airway inflammatory disease. Therefore, AGK2 is a good potential candidate for treating allergic asthma and lung inflammation.